2008
DOI: 10.1007/s00787-008-0706-8
|View full text |Cite
|
Sign up to set email alerts
|

Predictive factors of length of inpatient treatment in anorexia nervosa

Abstract: Nutzungsbedingungen

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
74
3
6

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(88 citation statements)
references
References 27 publications
5
74
3
6
Order By: Relevance
“…The BMI at the beginning of treatment as well as psychiatric comorbidity and purging behavior turned out to be very important factors that have been repeatedly found in a great number of studies [14,18,23,26]. In contrast, current age, age at onset, duration of AN, and BMI at discharge did not emerge as predictors in our study, whereas these factors have often been reported as predictors in AN outcome studies [10,23,28].…”
Section: Discussioncontrasting
confidence: 61%
“…The BMI at the beginning of treatment as well as psychiatric comorbidity and purging behavior turned out to be very important factors that have been repeatedly found in a great number of studies [14,18,23,26]. In contrast, current age, age at onset, duration of AN, and BMI at discharge did not emerge as predictors in our study, whereas these factors have often been reported as predictors in AN outcome studies [10,23,28].…”
Section: Discussioncontrasting
confidence: 61%
“…[21][22][23] Predictors of length of hospital stay are comparable to predictors of inpatient costs as both outcome variables are strongly correlated and describe resource consumption by the patient. 34,35 Strik Lievers et al 22 identified ''duration of AN,'' ''use of tube feeding,'' ''accomplishment of weight contract,'' ''number of previous inpatient stays,'' and ''presence of comorbid disorder (mood disorders, anxiety disorders, personality disorders)'' as significant predictors of LOS for inpatients. As far as comparable, this is in line with findings from our study, since comorbid mood disorders, among other things personality disorders increased inpatient costs significantly.…”
Section: Discussionmentioning
confidence: 99%
“…The reported lengths of stay in ED patients were relatively short in the United States and Canada (around 2-4 weeks) [22][23][24][25], but relatively long in the United Kingdom and France (around 4 months) [26,27]. The present study revealed that the mean length of stay in ED patients was about 2 months in Japan.…”
Section: Discussionmentioning
confidence: 43%